Leveraging Information Quality to Drive Sustainability Performance: Integrating TTF and TAM in Borobudur Temple’s Computerized AIS - Anissa Hakim Purwantini; Nur Laila Yuliani; Dyah Rizka Winarti; Diesyana Ajeng Pramesti; Ariq Fikria Niagasi (IECON: International Economics and Business Conference, 2025)
This study investigates how Computerized Accounting Information Systems (CAIS) and task–technology fit (TTF) shape employees’ perceived usefulness (PU) and, ultimately, sustainability performance in the heritage-tourism context of Borobudur Temple, Indonesia. Grounded in Task–Technology Fit theory and the Technology Acceptance Model (TAM), the study employed a purposive survey of 80 CAIS users. Data was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the hypothesized relationships among information quality, system quality, service quality, task characteristics, technology characteristics, TTF, PU, and sustainability performance. The results reveal that only information quality significantly enhances TTF, whereas system quality, service quality, task characteristics, and technology characteristics have no direct effect on TTF. TTF strongly predicts PU, which, in turn, positively influences sustainability performance. Theoretically, these findings extend TTF and TAM by showing that, in a heritage-tourism setting, high-quality information is the critical antecedent of TTF, while system quality, service quality, task characteristics, and technology characteristics are not significant. Practically, managers should prioritize improving the informational attributes of CAIS (accuracy, relevance, and timeliness) to increase user fit and perceived benefits, thereby fostering sustainable operational performance.